2013
DOI: 10.6116/kjh.2013.28.6.31
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-blind, Placebo-controlled Study to the efficacy and Safety of NMED-01 and NMED-02 in Mild Alcoholic Liver Subjects

Abstract: Objectives : The purpose of this study was to determine whether NMED-01 or NMED-02 improves laboratory test results in participants with liver function disorder. Methods : This is a randomized, placebo-controlled trial in which participants, treating physicians and data management staff were blinded to treatment group. The study was conducted at Semyung university oriental medicine hospital in Jecheon where participants with high level of serum γ-GTP (60-350 U/L) were enrolled. The intervention consisted of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…However, most evidence suggests that P. lobata and puerarin have hepatoprotective effects in animal models of hepatotoxicity [ 35 – 40 ]. Also, administration of P. lobata extract for 12 weeks did not affect ALT and AST levels in human subjects with elevated serum γ-glutamyl transferase levels due to alcohol consumption [ 41 ]. Baicalin, the major compound of S. baicalensis , has been reported to induce kidney injury and fibrosis in rats at high doses (≥ 400 mg/kg/day per os ); yet the highest administered baicalin dose in this study was approximately 200 mg/kg/day, which is lower than the reported toxic dose [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, most evidence suggests that P. lobata and puerarin have hepatoprotective effects in animal models of hepatotoxicity [ 35 – 40 ]. Also, administration of P. lobata extract for 12 weeks did not affect ALT and AST levels in human subjects with elevated serum γ-glutamyl transferase levels due to alcohol consumption [ 41 ]. Baicalin, the major compound of S. baicalensis , has been reported to induce kidney injury and fibrosis in rats at high doses (≥ 400 mg/kg/day per os ); yet the highest administered baicalin dose in this study was approximately 200 mg/kg/day, which is lower than the reported toxic dose [ 24 ].…”
Section: Discussionmentioning
confidence: 99%